Assessment of the glymphatic dysfunction in amyotrophic lateral sclerosis using the diffusion tensor imaging along the perivascular spaces index: a pilot study - Baek, Seol-Hee; Tae, Woo-Suk; Park, Jin-Woo; Kim, Byung-Jo (Frontiers in Aging Neuroscience, 2025)
BackgroundThe glymphatic system plays a critical role in clearing interstitial waste from the brain. Dysfunction of this system has been linked to various neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS). The diffusion tensor imaging-along the perivascular space (DTI-ALPS) index has emerged as a potential neuroimaging biomarker for evaluating glymphatic function. This study investigates whether glymphatic function differs in individuals with ALS compared to those with Parkinson's disease (PD) and normal controls (NCs), using the DTI-ALPS index.MethodsThis study included 35 ALS patients, 35 age- and sex-matched PD patients, and 13 NCs. Diffusion tensor imaging (DTI) was conducted, and the DTI-ALPS index was calculated. Clinical assessments included demographic data, disease duration, cognitive status, and functional scales. Group comparisons and correlation analyses were performed to assess the relationship between the DTI-ALPS index and clinical parameters.ResultsThe ALS group exhibited a significantly lower right-side DTI-ALPS index than the NC group (p = 0.037), while no differences were observed between the ALS and PD groups. The DTI-ALPS index was negatively correlated with age in ALS and PD groups but showed no correlation with clinical measures in the ALS group. Women in the ALS group had a significantly higher DTI-ALPS index than in men.ConclusionGlymphatic dysfunction may contribute to the pathogenesis of ALS, as evidenced by a reduced DTI-ALPS index compared to NCs. However, its clinical relevance and specificity for ALS remain uncertain. Further studies with larger cohorts are warranted to validate these findings.